(untitled) (Research, Society and Development, 2021)
This study aims to present the creation process, methodology, and evaluation of a musical prototype called Melôkids. It is a digital resource for Music Education aimed at the early years of Elementary School, remotely developed as a result of the Covid 19 pandemic, in the context of a Master’s course. To achieve the general objective, the following specific objectives are: to demonstrate which strategies were used to make decisions about the prototype’s type and target audience; detail the product creation process, according to the design thinking methodology taught during the course and aspects of human-computer interaction (HCI); and report the evaluations carried out by professionals (teachers and specialists) and end-users, identifying the problems found in the prototype. The research was applied in nature, followed by a qualitative approach, and used action research in its procedures. As a result, the article reveals strategies operated in remote teaching for the production of musical prototypes, such as: the interdisciplinary content that involved its development; the Integration of the Methodology Adopted by the Teachers of the Discipline (Design Thinking) with the Methodology Used by the Team (Use of HCI Concepts to Improve the Tool); the use of the Scratch language for programming digital resources; the platforms and digital resources found to adapt activities in the remote format (Google Meet, SOLAR, WhatsApp, Trello, and Sebrae Canvas); and finally, the procedures used to evaluate the prototype, which identified the need to implement improvements in the tool.